Valued attributes of professional support for people who repeatedly self‐harm: A systematic review and meta‐synthesis of first‐hand accounts. (15th January 2022) - Sass, Cara; Brennan, Cathy; Farley, Kate; Crosby, Helen; Rodriguez Lopez, Rocio; Romeu, Daniel; Mitchell, Elizabeth; House, Allan; Guthrie, Else
Abstract: Therapeutic interventions are an important adjunct to self‐help strategies for people who self‐harm. There is little guidance for those offering therapy on the effective components of interventions for people who self‐harm. This was a systematic review aiming to identify the factors that contribute to positive experiences of therapy as described by people who have reduced or stopped self‐harm. The review followed PRISMA guidelines to locate and synthesize peer‐reviewed qualitative studies describing experiences of therapy among people who had reduced or stopped self‐harm. Study selection, data extraction, and quality assessment were peer reviewed and conducted for at least two researchers independently. Relevant first‐hand quotations were extracted from eligible studies and synthesized using a thematic analysis in collaboration with experts with personal and professional experience of self‐harm. Twenty‐three studies met eligibility criteria. Themes identified in the reported accounts were arranged under two meta‐themes. 'Positive aspects of seeing a professional' identified aspects of professional care that were common to all encounters: the value of sharing, space to talk and reflect, and the boundaries inherent in contact with a professional. 'Positive attributes of individual professionals' depended upon individual characteristics: the ability to build reciprocal trust by being non‐judgemental, showing genuine empathic concern, and being confident to talk about and respond directly to self‐harm. Our review indicates that therapeutic alliance is perceived as key to effective professional help for self‐harm, irrespective of underlying principles of therapy. All forms of therapy should be timely and reliable and centred around the needs of the individual and their experience of self‐harm.